Effects of BF Gene Polymorphism on the Reproductive Performance of Hybrid Polish Landrace X Polish Large White Sows - Napierała Dorota; Kawęcka Maria; Jacyno Eugenia; Matysiak Beata; Kołodziej-Skalska Anita (Acta Veterinaria, 2016)
The aim of this study was to determine the potential relationship between variants of the BF gene and litter size in Polish Landrace x Polish Large White sows. To identify polymorphism within the BF gene, the PCR-RFLP method was applied, using specific primers and the SmaI enzyme. The researchers identified the presence of two alleles, T and C, with frequencies: 0.68 and 0.32, giving three genotypes with frequencies: 0.49, 0.37 and 0.14, respectively for TT, TC and CC. Analysis of relationships between the various genotypes of the BF gene and selected reproductive traits showed significant differences. Sows with TT genotype in the BF locus, gave birth to significantly more live piglets in the first litter (10.24) compared with sows with the CC genotype (7.13).